2021
DOI: 10.1111/jpm.12796
|View full text |Cite
|
Sign up to set email alerts
|

Development and psychometric properties of the Therapeutic Relationship Assessment Scale‐Nurse

Abstract: Accessible Summary What is known on the subject? The literature shows a clear relationship between a good therapeutic relationship (TR) and the efficacy of nursing interventions. For the implementation of nursing psychotherapeutic interventions, the initial establishment of a good TR is essential. Several instruments assess the relationship established between the therapist and the patient in psychotherapy. However, no tool has been found to assess the quality of the TR established between the nurse and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 41 publications
0
9
0
8
Order By: Relevance
“…As a result of EFA, it was seen that the Turkish version of the scale preserved its original structure and had a strong factor structure for the Turkish sample. In the study of Coelho et al (2021), all 25 items had a factor load of at least 0.30 in the sub-dimension.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…As a result of EFA, it was seen that the Turkish version of the scale preserved its original structure and had a strong factor structure for the Turkish sample. In the study of Coelho et al (2021), all 25 items had a factor load of at least 0.30 in the sub-dimension.…”
Section: Discussionmentioning
confidence: 98%
“…The original TRAS-Nurse consists of 25 items (Coelho et al, 2021). It has been reported that the scale can be used in one dimension as well as in four sub-dimensions (Empathy, Self-knowledge, Involvement, Orientation).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants' demographic information was obtained through a questionnaire. The quality of the nurse–patient therapeutic relationship from the nurse's perspective was also obtained through The Therapeutic Relationship Assessment Scale–Nurse (TRAS‐Nurse; Coelho et al, 2021). This scale was administered to all participants prior to the interview.…”
Section: Methodsmentioning
confidence: 99%